CoVITEST: A Fast and Reliable Method to Monitor Anti-SARS-CoV-2 Specific T Cells From Whole Blood - Egri, Natalia; Olivé, Victoria; Hernández-Rodríguez, José; Castro, Pedro; De Guzman, Catherine; Heredia, Libertad; Segura, Ana Castellet; Fernandez, M. Dolores; de Moner, Noemi; Torradeflot, María; Ballús, Judit; Martinez, Robert; et al. (Frontiers in Immunology, 2022)
Cellular and humoral immune responses are essential for COVID-19 recovery and protection against SARS-CoV-2 reinfection. To date, the evaluation of SARS-CoV-2 immune protection has mainly focused on antibody detection, generally disregarding the cellular response, or placing it in a secondary position. This phenomenon may be explained by the complex nature of the assays needed to analyze cellular immunity compared with the technically simple and automated detection of antibodies. Nevertheless, a large body of evidence supports the relevance of the T cell’s role in protection against SARS-CoV-2, especially in vulnerable individuals with a weakened immune system (such as the population over 65 and patients with immunodeficiencies). Here we propose to use CoVITEST (Covid19 anti-Viral Immunity based on T cells for Evaluation in a Simple Test), a fast, affordable and accessible in-house assay that, together with a diagnostic matrix, allows us to determine those patients who might be protected with SARS-CoV-2-reactive T cells. The method was established using healthy SARS-CoV-2-naïve donors pre- and post-vaccination (n=30), and further validated with convalescent COVID-19 donors (n=51) in a side-by-side comparison with the gold standard IFN-γ ELISpot. We demonstrated that our CoVITEST presented reliable and comparable results to those obtained with the ELISpot technique in a considerably shorter time (less than 8 hours). In conclusion, we present a simple but reliable assay to determine cellular immunity against SARS-CoV-2 that can be used routinely during this pandemic to monitor the immune status in vulnerable patients and thereby adjust their therapeutic approaches. This method might indeed help to optimize and improve decision-making protocols for re-vaccination against SARS-CoV-2, at least for some population subsets.